Eco-friendly formulation of wild Bacillus thuringiensis secondary metabolites through molecular characterization against the lepidopteran pest. (January 2018) - Chandrasekaran, Rajamanickam; Revathi, Kannan; Senthil-Nathan, Sengottayan; Kalaivani, Kandaswamy; Hunter, Wayne B.; Duraipandiyan, Veeramuthu; Al-Dhabi, Naif Abdullah; Esmail, Galal Ali
Abstract: Continuous applications of Bt in agricultural fields has resulted in the selection of resistant streams of Lepidoptera pests. Hence an attempt is made to find out a wild-type highly virulent strain of Bt from soil samples. The 16S rRNA sequencing was done with Gen Bank accession number (KF543356 ). Screening for Cry genes was carried out using PCR. Secondary metabolites were partially purified and identified through chromatogram and GC-MS. Further analysis was done to identify the compound structure and molecular formula from the hexane extract of the Bt secondary metabolites. The effective concentration of the Bt metabolites were also determined in this study. Secondary metabolites isolated from the Bt strain showed strong effects on the lepidopteran, Helicoverpa armigera, Hübner. Glutathione-S-transferase activity against secondary metabolites was decrease in third through fifth instars at a concentration of 250 mg/ml. At the lowest concentration there were slight changes in cytochrome activity of H. armigera . The secondary metabolites from new wild strains of Bt may provide effective biopesticide products. Also the Bt isolates could be used in to produce recombinant Bt rice plant in order to develop any resistant against the Bt formulation. Graphical abstract: Highlights: Highly virulent strain of Bt from soil samples were isolated with 16S rRNA sequencing. Cry genes was carried out using PCR and secondary metabolites were purified and identified through chromatogram and GC-MS. The secondary metabolites isolated from the Bt strain showed strong effects on Helicoverpa armigera, including Glutathione-S-transferase enzyme inhibition.